Investigation of eggshell as catalyst on the torrefaction of empty fruit bunch - Esther Hui Xian Lim (KeAi Communications Co., Ltd., 2021)
Biomass derived energy is considered as a sustainable energy. However, the utilization of biomass as a solid fuel has many challenges such as low energy density, high moisture and volatile matter content. Hence, torrefaction is one of the thermal treatments applied to enhance the fuel properties of biomass. The objective of this research was to investigate the influence of calcium-based catalyst on the torrefaction of empty fruit bunch (EFB). Waste eggshell was utilized as Ca source as it stands to be beneficial in terms of availability and cost. The effect of torrefaction parameters such as temperatures from 200 °C to 300 °C, residence times from 30 min to 90 min, and the catalyst amounts from 0 wt% to 15 wt% were investigated. Among the three process parameters, temperature had the most significant effect on mass and energy yield. However, the effect of residence time and the catalyst loading was relatively insignificant. With the increment in torrefaction temperature, higher heating value (HHV) and carbon content in torrefied biomass increased. After catalytic torrefaction, the torrefied biomass displayed increment on cellulose crystallinity and volatile matter content. Moreover, the surface structure of catalytic torrefied biomass at 300 °C was turned into highly fibrous surface due to degradation of lignin. The results from this study concluded that the eggshell catalyst did not alter the characteristics of solid fuel significantly in torrefaction.